Manajemen Risiko Pada Bank Pembangunan Daerah Jawa Barat dan Banten Tbk - Lutfi Alif Tiyani; Diah Febriyanti; Siti Ummi Munawaroh; Ulin Ni’mah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
This study aims to identify and analyze risk management in banking, namely risk, operational risk, market risk, liquidity risk, legal risk, compliance risk, yield risk and investment risk. And to analyze the financial ratio reports for the first quarter and second quarter of 2020 at the West Java and Banten (BJB) Tbk development bank. This research uses descriptive quantitative method at PT. West Java and Banten Regional Development Bank Tbk (BJB) Tbk which are listed on the Indonesia Stock Exchange during the period 2018 to 2020. The sample in this study is PT. West Java Regional Development Bank and Banten Tbk (BJB) which are registered on the IDX and are still operating in the 2018-2020 period. Data collection tools in this study are to use the method of observation on financial data at the bank and internet research. The results of this study indicate the existence of smooth and bad conditions in management analysis and financial ratio analysis at BJB banks which consist of analysis of CAR, non-performing assets, CKPN, gross NPF, NPF Net, ROA, ROE, NI, NOM, BOPO, and FDR. The results of the overall calculation at PT. West Java Regional Development Bank and Banten Tbk, in the 2018-2020 period experienced an increase and decrease every year.